Herbicidas sistemático y de contacto en el control de orejilla (Geophilia macro poda) en el cultivo de banano orito (Musa acuminata, AA). Valencia-Los Róos.2013 - Veliz Carbo, Franklin Leonel (2014)
This research was conducted during the months of November to January 2013 on the farm “SAN FRANCISCO " From Company: REYBANPAC, located in the canton Valencia - via Los Rios province, Valencia - La Mana. The experimental design used in this research was the Complete Random Design (CRD) with 5 treatments and 4 repetitions performed well in this investigation the Tukey test at 5% probability, research allowed us to evaluate the levels of control orejilla weed in banana plantations treated with products and absolute control. Thus based on the results can be analyzed variables weed control level on. The main objective is raised: will evaluate the effect of three herbicides, systemic and two contacts for control orejilla (Geophila macropoda) Banana cultivation in Orito. As specific objectives: 1) will determine the efficiency of a systemic herbicide, two of contact and the mix of the two on orejilla control, 2) Determine the costs of herbicide applications per treatment. The results showed that : 1) Most control effect with the first application was observed in the treatments, T4 (+ Screeds Hervax -3), with an average of 85 % control, followed by T3 (Correctors), averaging 80.63 % of control, and while the second application .........................................................................